Crisis and opportunity: Transforming climate governance for SMEs - Hampton, S; Blundel, R; Eadson, W; Northall, P; Sugar, K (Elsevier, 2023)
Small and medium-sized enterprises (SMEs) are key actors in climate change mitigation and adaptation. Their aggregate emissions are significant, and they are disproportionately affected by climate impacts, including extreme weather events. SMEs also play a vital role in shaping the environmental behaviours of individuals, communities, and other businesses. However, these organisations have been largely neglected by climate policies across all levels of government. A series of global crises, including the COVID-19 pandemic, war in Europe and the Middle East, and energy price spikes, have posed an existential threat to millions of SMEs, while also acting as a catalyst for the reconfiguration of the social contract between business, society and the state, both temporary and more long-term. In this article, we make the case for increased focus on the governance of SME decarbonisation to address this turbulent context. We outline key challenges facing public policymakers and other governance actors, compare strategic options, identify evidence gaps that hinder effective interventions, and highlight implications for research. In doing so we set out key elements of a renewed social contract for business, society and state relations.